Environmental Impact Assessment of Automatic Brick Manufacturing Project at Lebukhali Dumki (Journal of Environmental Science and Natural Resources, 2019)
The study has been conducted at USA Agro and Auto Bricks Ltd. at Lebukhali, Dumki Upazila under Patuakhali district. The purpose of this study is to find out the potential environmental impact during the construction operation and maintenance phase of the project and suggest effective mitigation measures to reduce negative impacts. Data necessary for the study has been collected through both primary and secondary data sources by literature review, Household Questionnaire Survey, Focus Group Discussion, and Key Informant Interview of surrounding people. Environmental Impact is analyzed through the calculation of Environmental Impact Value and Leopold matrix. Environmental Impact Value (+2) shows that the impact of the brickfield is low positive. Leopold matrix shows the pre, during and post construction value as 2.28, 1.56 and 1.82 where pre-impact is moderate, during and post-impact is low. Our estimated result shows that the negative impact of the project is minimum.J. Environ. Sci. & Natural Resources, 11(1-2): 87-95 2018